Digital Twin Aided Sustainability Assessment of Modern Light Rail Infrastructures - Borjigin, Aorigele Orgil; Sresakoolchai, Jessada; Kaewunruen, Sakdirat; Hammond, John (Frontiers in Built Environment, 2022)
This study aims to evaluate the whole life cycle performance of Precast Advanced Track (PCAT) light rail systems in a digital-twin environment, which is timesaving, flexible, and highly accurate. Two sustainability aspects of the system are addressed: environmental and economic impacts. In the life cycle assessment (LCA), energy consumptions and CO2 emissions are calculated, whereas costs at each stage were calculated and converted to present values in the life cycle costing assessment (LCC). Revit has been used for the assessment. Revit enables the bill of quantities in the models in order to provide the quantitative data for the sustainability assessments. In the PCAT light rail systems, all of structures and components have been considered, including subbase, concrete slab, rail fastening, rails, bituminous layer, rubber pad, and grease lubrication. The results exhibit that concrete slabs for street and off-street systems have a minor contribution to minimising energy consumption, CO2 emissions, and costs. Rail fastenings and rails can be recycled, but the energy consumptions are relatively enormous. Unrecyclable materials such as bitumen and grout account for a large portion of lifecycle CO2 emissions and costs. Surprisingly, these two materials are quite sensitive to the parametric change. The digital twin accordingly confirms that PCAT concrete slabs demonstrate a good performance throughout the whole life cycle. However, there is still room for improvements to take place, for example: re-design a concrete slab with less grout while showing good waterproof performance. These structural modifications can be updated on the digital twin to enact positive changes for sustainable development of light rail systems.